Gut morphology, immunocompetence, blood and meat quality profile of broiler chickens fed turmeric (Curcuma longa) oil as an antibiotic substitute - GOBIRAJU, S; VASAN, P; RAJENDRAN, K; PURUSHOTHAMAN, M R (The Indian Journal of Animal Sciences, 2019)
The present investigation was carried out to study the antibiotic efficacy of turmeric oil in commercial broiler chicken. Day-old broiler chicks (144) were randomly divided into six treatment groups with four replicates of six chicks each. The experimental diets were corn – soya meal basal diet (T1), basal diet + antibiotic (500 ppm oxytetracycline-T2), basal diet + 0.025% turmeric oil (T3), 0.050% turmeric oil (T4), 0.075% turmeric oil (T5) and 0.100% turmeric oil (T6) respectively. The birds were reared under standard managemental practices for 42 days. The levels of serum total protein, albumin, globulin, serum total cholesterol, HDL cholesterol, LDL cholesterol, triglycerides and breast meat cholesterol were not influenced either by the supplementation of antibiotic or by the supplementation of turmeric oil at graded levels. Neither antibiotic nor turmeric oil supplementation had any significant effect on the gut microbial population (total microbes, Lactobacillus, E. coli and Clostridium) and length of ileal villi of broiler chicken. Turmeric oil supplementation at 0.025 and 0.050% levels led to significant reduction in crypt depth than that of antibiotic supplemented group. Dietary supplementation of turmeric oil at 0.025 and 0.100% levels showed higher profit (` 0.32 and 1.03/kg live weight gain respectively) when compared to antibiotic supplemented group. It could therefore be concluded that supplementation of turmeric oil at 0.025% level instead of antibiotic feed additive would produce similar effect on serum lipid profile, meat quality, gut microbial load and intestinal morphology in broiler chicken.